Análisis de las tics y su incidencia en el aprendizaje en informática en los estudiantes del 1er curso de bachillerato de la Unidad Educativa Prócer José de Antepara de la ciudad de Vinces en el periodo 2021- 2022 - Arreaga Leon, Ruben Antonio (2022)
The work presented below deals with the analysis of ICT and its impact on learning in students of the 1st year of Baccalaureate of the Prócer José de Antepara Educational Unit, whose general objective is to contribute and identify the different resources used for the process, administration and distribution of information and communication technology, as well as to write the importance of relating ICTs and their influence on the learning of computer science students at the time of receiving classes. In addition, the problem that exists today will be identified due to the fact that students, having virtual classes, have seen the need to have to buy technological devices with internet access, either to receive classes or carry out the different activities that the teacher tutor has, many times this technology is not used properly by students becoming a means of distraction directly affecting their academic performance. The results obtained by means of surveys carried out on the students of the aforementioned institution and interviews with teachers will also be analyzed, which will strengthen the theoretical support of this research, based on direct opinions. Concluding that ICTs are a very important digital tool for education since, thanks to this, students can access a vast amount of information, can share experiences, carry out work regardless of time and distance, it should be emphasized that, There is more fluid communication between the teacher and the student. Finally, as a recommendation, it is important to adapt the use of Information and Communication Technologies in accordance with the class objectives, which must be clear, precise and concise, previously established in order to choose the ICTs that most benefit the student. students in every situation that is presented in class.